Applying biorthogonal and orthogonal wavelets basis functions to the method of moments for modeling the helix antenna - Bayjja, Mohamed; Alsharahi, Gamil; Amhaimar, Lahcen; Amar Touhami, Naima; Aghoutane, Mohamed (Journal of electromagnetic waves and applications, 2021)
An efficient moment-method algorithm for analyzing helix antenna is presented. This algorithm is developed based on solving the helix integral equations using two categories of continuous wavelets-like basis functions, Biorthogonal and Orthogonal wavelets. In the first part, the current in the helix antenna is obtained using the method of moments with the triangle basis and pulse testing functions. Secondly, the orthogonal (Daubechies and Symlets) and the biorthogonal (spline generated biorthogonal) wavelets are used and compared in solving the helix integral equation. The grounds of comparison between the two categories are accurate in characterizing the induced current, matrix sparsity, relative error and computation time. The advantages and limitations of solving integral equations with each of the two wavelet categories are discussed. The numerical example is provided to demonstrate the validity and applicability of our proposed algorithm which can be easily implemented to produce a desired accuracy.